Pop, Power and Politics: Kiwi FM and the ‘Third Way’ in New Zealand - Mollgaard, Matthew (MEDIANZ, 2016)
In 2005 a major multi-national media company launched a New Zealand radio network that played only New Zealand music—Kiwi FM. Within a year it was clear that the experiment had failed, with the network attracting only negligible audience ratings and unsustainable commercial revenue. It was at this point that the New Zealand government stepped in, granting the network free broadcasting spectrum and significant funding in return for the ongoing promotion of New Zealand music. How this happened provides critical insights into ‘third way’ approaches to the creative industries, and in particular, local music as a cultural, political and economic commodity. Kiwi FM raises questions about national musical cultures and how artists, governments and businesses interact in these contested spaces. This article explores Kiwi FM as it moved from being a commercial enterprise to a government partner from behind the scenes, using previously unseen documents and interviews with key players in order to interrogate the utility of ‘third way’ approaches to promoting and supporting the creative industries.